Character Strength and virtues in The Perspective Of Islamic Education Psychology and Implication in Guidance and Counseling Services - Alivermana Wiguna; Jayadi Jayadi; Agus Heriyanto; Fatimah Setiani; Gita Anggraini; Harun Joko Praytno; Gamal Abdul Nasir Zakaria (Universitas Ahmad Dahlan, 2020)
The main objective of this study is to identify and formulate the strengths of character and virtue, according to Ibn Miskawaih and Imam Al-Ghazali. The study was carried out with a qualitative approach with the type of literature review, by tracing both books, especially journals related to the strength of character and virtues formulated by positive psychology. The data analysis was carried out in a descriptive-reflective-introspective way with the perspective of Islamic psychology. The results of the study show that in terms of the number and composition of the strengths of character and values of virtue developed by positive psychology and the psychology of Islamic education, which in this case is represented by the thoughts of Ibn Miskawaih and Imam Al-Ghazali, are not significantly different. There is little difference between the strength of the character of positive psychology and the psychology of Islamic education. The difference is that there is a middle point or middle way in the thoughts of Ibn Miskawaih and Imam Al-Ghazali. The shari'ah commands this midpoint or middle path; the goal is to achieve an intermediate path to all the qualities and qualities of virtue; if it deviates towards one of the two extremes, then it must be corrected. These findings can provide a valuable contribution to guidance and counseling services through strengthening character and virtue in the current era of global communication.